FLOWERING LOCUS T Improves Cucumber Adaptation to Higher Latitudes. Issue 2 (16th December 2019) - Wang, Shenhao; Li, Hongbo; Li, Yangyang; Li, Zheng; Qi, Jianjian; Lin, Tao; Yang, Xueyong; Zhang, Zhonghua; Huang, Sanwen
Abstract : Two large deletions upstream from FLOWERING LOCUS T occurred independently in Eurasian and East-Asian cucumber populations and are associated with higher expression of this gene and earlier flowering. Abstract: Flowering time plays a crucial role in the geographical adaptation of most crops during domestication. Cucumber ( Cucumis sativus ) is a major vegetable crop worldwide. From its tropical origin on the southern Asian continent, cucumber has spread over a wide latitudinal cline, but the molecular mechanisms underlying this latitudinal adaptation and the expansion of domesticated cucumber are largely unclear. Here, we report the cloning of two flowering time loci from two distinct cucumber populations and show that two large deletions upstream from FLOWERING LOCUS T ( FT ) are associated with higher expression of FT and earlier flowering. We determined that the two large deletions are pervasive and occurred independently in Eurasian and East-Asian populations. Nucleotide diversity analysis further revealed that the FT locus region of the cucumber genome contains a signature for a selective sweep during domestication. Our results suggest that large genetic structural variations upstream from FT were selected for and have been important in the geographic spread of cucumber from its tropical origin to higher latitudes.